Emerging Trends of Virtual Laboratories in Vocational Education: A Bibliometric Analysis - Deris Oktageri; Sukardi; Usmeldi; Wagino Wagino; Hansi Effendi (Universitas Pendidikan Ganesha, 2025)
Research on virtual laboratories has shown significant growth but is still scattered across disciplines and approaches. This condition indicates the need for systematic mapping in the context of vocational education to understand the development and direction of current research. This study aims to analyze international publications related to virtual laboratories in vocational education, covering research trends, highest citations, leading countries, and relevant publication sources. A quantitative approach with bibliometric analysis was used on 163 of the Scopus database from 2010 - 2024. Data were collected using the keywords